Impact of organ donation on grief symptoms in donor families - Marzieh Latifi; Elahe Pourhosein; Mohammad Tagi Talebian; Iman Seyhoun; Ehsan Alibeigi; Mohammadmehdi Seyed Nasseri; Sanaz Dehghani (BMC Psychology)
Abstract Introduction The aim of the study was to identify the factors that influence grief among donor families regarding organ donation. Methods This cross-sectional study, utilizing an analytical approach, employed a convenience sampling method to gather data from family members. Over the three years, all families who consented to organ donation were invited to participate, from all, 222 questionnaires were completed by donor family members who had given consent and successfully proceeded with the donation. We collected data using the Grief Experience Questionnaire (GEQ-34). Descriptive and analytic statistics were utilized to determine the factors influencing grief using SPSS 18 software. A significance level of P < 0.05 was considered statistically significant for all analyses. Results The donor gender was mostly male (153, 68.9%) with a mean age of 35.96 ± 17.05 (range: 2–68) years at the time of death. The mean score of GEQ was 93.3 ± 22.4 (ranging from 39 to 141) from a theoretical range of 34 to 170 with the higher the score indicating a more intensive grief experience. 23(10.4%), 100 (45%), and 99 (44.6%) of participants suffered from low (GEQ 34–68), moderate (GEQ 69–102), and high levels of grief (GEQ higher than 103), respectively. Guilt had the highest mean score among different aspects of the GEQ component. A significant negative relationship between guilt, age of the donor (r=- 0.10, P < 0.011), and time interval from donation (r=-0.17, P < 0.001), showed that guilt may be more pronounced in cases involving younger donors or more recent losses. Families of suicide-related brain death cases, and those who lost their children rather than their spouses, experienced more grief compared to other families. Additionally, families with prior knowledge of the concept of brain death experienced lower grief compared to those without such knowledge. Conclusion The results reveal that the average grief score among the donors’ families was higher than normal, with 89.1% experiencing moderate to severe levels of grief. While the results may seem challenging due to the high prevalence of grief, they offer valuable insights into how support systems and education can be tailored to better assist families in coping with their loss. Clinical trial number Not applicable.